2019
DOI: 10.1016/j.jimonfin.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Short and medium term financial-real cycles: An empirical assessment

Abstract: Theories such as Minsky's financial instability hypothesis or New Keynesian financial accelerator models assign a key role to financial factors in business cycle dynamics. We present descriptive statistics and a simple estimation framework to examine the financial-real interaction mechanisms that are at the core of these theories. Specifically, we examine cycle frequencies in seven OECD countries over the period 1970 to 2015, and find that interest rates, business debt, and household debt exhibit cycle lengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…depreciation), while the currency behaves like a predator that grows together with the prey. Stockhammer et al (2019) argue that such an endogenous real-financial interaction mechanism lies at the heart of theories of financial-real cycles such as Hyman Minsky's Financial Instability Hypothesis (Minsky, 2008(Minsky, [1975(Minsky, ], 2016(Minsky, [1982; for a survey see Nikolaidi and Stockhammer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…depreciation), while the currency behaves like a predator that grows together with the prey. Stockhammer et al (2019) argue that such an endogenous real-financial interaction mechanism lies at the heart of theories of financial-real cycles such as Hyman Minsky's Financial Instability Hypothesis (Minsky, 2008(Minsky, [1975(Minsky, ], 2016(Minsky, [1982; for a survey see Nikolaidi and Stockhammer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we focus on credit-to-GDP growth in five years, log(credit-to-GDP t )log(credit-to-GDP t-20 ) relative to its mean. However, some authors argue that longer periods better capture sustained credit growth, signaling the Earlier studies identified structural connections between credit growth and output, such that countries with financially driven business cycles and countries with faster credit growth before the 2007 crisis experienced deeper and more prolonged recessions (Stockhammer et al, 2019;Bezemer and Zhang, 2019).…”
Section: Credit-to-gdpmentioning
confidence: 99%
“…Due to the availability of shorter time series in the case of Kazakhstan in general, we are constrained on choosing 20 quarters windows. Earlier studies identified structural connections between credit growth and output, such that countries with financially driven business cycles and countries with faster credit growth before the 2007 crisis experienced deeper and more prolonged recessions (Stockhammer et al , 2019; Bezemer and Zhang, 2019).…”
Section: Datamentioning
confidence: 99%
“…These cycles tend to be longer than regular business cycles, with roughly double their duration. Stockhammer et al (2018a) test for endogenous cycle mechanisms based on simple debt cycle Minsky models, where cycles are generated from the interaction of a financial and a real variable, by using a VAR methodology for seven advanced economies. They estimate a series of 2D systems and test for complex eigenvalues and whether the relevant coefficients have the predicted signs.…”
Section: Testing For Endogenous Financial-real Cyclesmentioning
confidence: 99%
“…. Strictly speaking,Stockhammer et al (2018a) test two necessary conditions for the cycles and test the interaction mechanism that can generate a cycle.An update on Kalecki-Minsky modelling 185 © 2019 The Author Journal compilation © 2019 Edward Elgar Publishing Ltd Downloaded from Elgar Online at 09/01/2020 08:21:24PM via free access…”
mentioning
confidence: 99%